2014
DOI: 10.1017/jsc.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends and Impact of Smoking Cessation Interventions for Adult Smokers in Low and Middle Income Countries: A Systematic Literature Review

Abstract: Objective: This study aims to systematically review the existing literature on the current developments and impact of smoking cessation interventions targeted toward adult smokers in low and middle income countries (LMICs).Methods: Major databases were searched with the following selection criteria: (1) studies based on empirical findings that demonstrate the impact of smoking cessation interventions in LMICs; (2) studies conducted in or focused on LMICs; (3) studies targeted at the adult smoking population; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This framework mandate countries to take more stringent measures on tobacco control, particularly in monitoring, smoke-free policies, cessation program, warnings, advertising ban, and tobacco taxation [ 55 ]. The government should focus on promoting the coverage and accessibility of smoking cessation interventions, which are culturally appropriate [ 56 ]. While Indonesia has integrated “offer help to quit tobacco” as a part of the WHO Package of Essential NCD (WHO PEN) interventions in the primary health care, [ 57 ] only 34.6% of smokers who visited healthcare providers received advice to quit smoking [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This framework mandate countries to take more stringent measures on tobacco control, particularly in monitoring, smoke-free policies, cessation program, warnings, advertising ban, and tobacco taxation [ 55 ]. The government should focus on promoting the coverage and accessibility of smoking cessation interventions, which are culturally appropriate [ 56 ]. While Indonesia has integrated “offer help to quit tobacco” as a part of the WHO Package of Essential NCD (WHO PEN) interventions in the primary health care, [ 57 ] only 34.6% of smokers who visited healthcare providers received advice to quit smoking [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, two systematic reviews and a scoping review have identified several observational or randomized controlled studies assessing the efficacy of smoking cessation interventions in LMICs [16][17][18] however, none of them focused upon economic evaluations that evaluated both the cost and effectiveness of those interventions.…”
Section: Although Several Tobacco Control Interventions Have Been Foundmentioning
confidence: 99%
“…Undertaking a systematic literature review, Owotomo (2014) reported that smoking cessation interventions in low-and middleincome countries are not generally available and affordable for adults, and therefore costeffective and culturally appropriate interventions are needed. The situation is similar for adolescents.…”
Section: Interventions In Chinamentioning
confidence: 99%